La 3D au service de la conservation des grottes ornées, l’exemple de Lascaux et du simulateur Lascaux - Delphine Lacanette; Philippe Malaurent (In Situ)
Numerical simulation in fluid mechanics is applied here to the conservation of the patrimony and more particularly to the Lascaux cave, in Dordogne, France. A very accurate 3D laser survey of the cavity of more than 150 million points was used as a base of the Lascaux simulator, a numerical tool allowing to test in laboratory, on a computer, the modifications to bring eventually to the cave, and to check the way it reacts before achieving these modifications in situ. The simulator is an innovative conserving tool for preventive conservation.